Risk externalities in a payments oligopoly - Tore Nilssen (University of Oslo, Department of Economics, 2000)
This paper discusses an oligopoly where firms exert negative externalities upon each other. A theoretical model is developed for a market where these externalities are particularly relevant: the intra-day credit market, which is crucial for the operation of an efficient payments system. A central bank participating actively in this market has two features that distinguishes it from the other banks: first, it is a publicly owned bank and may therefore be considered as maximizing welfare; secondly, it cannot become illiquid, and therefore it does not impose any systemic risk on other banks. The equilibrium outcome in this case is compared to the social optimum and to the equilibrium in a situation where the publicly owned bank is an ordinary one and thus can become illiquid.
Keywords: D43; G21; E58; L32; 330; Kreditgeschäft; Externer Effekt; Risiko; Oligopol; Theorie